Assessing the impact of country culture on the socio-cultural practice of radiography. Issue 4 (November 2020) - Cowling, C.; Lawson, C.
Abstract: Introduction: Diagnostic radiography is a deceptively similar occupation regardless of country and yet there are wide varieties of scopes of practice, levels of autonomy, respect and understanding of what a radiographer does. Methods: A socio-cultural comparative ethnographic study was carried out in seven culturally diverse countries observing and interviewing radiographers in one regional hospital in each country. The thick descriptions collected were thematically analysed. This article describes the comparison between work culture and country culture between the seven countries using the analytic device of Hofstede's cultural dimensions. Results: The results demonstrate a wide disparity between countries, in importance of hierarchy, acceptance of individuality, ability to work autonomously and strength of country specific cultural norms. The impact of the country culture on the practice of radiography is manifested through variations in education, scope of practice, and level of recognition within the healthcare spectrum. Conclusion: These findings offer insight into the socio-cultural practice of radiography through an ethnographic cultural-specific lens and provide some explanations for the barriers evidenced currently to global recognition of standards and scopes of practice. Implications for practice: The study introduced empirical evidence into a subject matter hitherto unexplored in a global comparative manner, and creates an opportunity to improve the recognition of radiographers by creating a foundation of research upon which to build further more targeted studies.